Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives

NOx catalyzed pathway of stratospheric ozone depletion: a coupled cluster investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2012)
We report a theoretical investigation on the NOx catalyzed pathways of stratospheric ozone depletion using highly accurate coupled cluster methods. These catalytic reactions represent a great challenge to state-of-the-art ab initio methods, while their mechanisms remain unclear to both experimentalists and theoreticians. In this work, we have used the so-called ``gold standard of quantum chemistry,'' the CCSD(T) method, to identify the saddle points on NOx-based reaction pathways of ozone hole formation. Energies of the saddle points are calculated using the multireference variants of coupled cluster methods. The calculated activation energies and rate constants show good agreement with available experimental results. Tropospheric precursors to stratospheric NOx radicals have been identified, and their potential importance in stratospheric chemistry has been discussed. Our calculations resolve previous conflicts between ab initio and experimental results for a trans nitro peroxide intermediate, in the NOx catalyzed pathway of ozone depletion.

Highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of alpha-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, Menaka; Chowdhury, Partha Sarathi; Dutta, Achintya Kumar; Kumar, Pradeep; Pal, Sourav (RSC Advances, 2013)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed alpha-amination of aldehyde and one-pot indium mediated allylation of the crude alpha-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.

Performance of the EOMIP-CCSD(2) method for determining the structure and properties of doublet radicals: a benchmark investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2013)
We present a benchmark study on the performance of the EOMIP-CCSD(2) method for computation of structure and properties of doublet radicals. The EOMIP-CCSD(2) method is a second-order approximation to the standard EOMIP-CCSD method. By retaining the black box nature of the standard EOMIP-CCSD method and adding favorable N-5 scaling, the EOMIP-CCSD(2) method can become the method of choice for predicting the structure and spectroscopic properties of large doublet radicals. The EOMIP-CCSD(2) method overcomes the typical problems associated with the standard single reference ab initio treatment of doublet radicals. We compare our results for geometries and harmonic vibrational frequencies with those obtained using the standard EOMIP-CCSD method, as well as unrestricted Hartree-Fock (UHF)- and restricted open-shell Hartree-Fock (ROHF)-based single-reference coupled-cluster and second order many-body perturbation theory (MBPT(2)) methods. The effect of the basis set on the quality of the results has been studied using a hierarchy of Dunning's correlation-consistent aug-cc-pVXZ (X = D, T, Q) basis sets. Numerical results show that the EOMIP-CCSD(2) method, despite its N-5 scaling, gives better agreement with experimental results, compared to the UHF- and ROHF-based MBPT(2), as well as the single-reference coupled-cluster methods.

Perturbative approximations to single and double spin flip equation of motion coupled cluster singles doubles methods - Dutta, Achintya Kumar; Pal, Sourav; Ghosh, Debashree (Journal of Chemical Physics, 2013)
Spin flip equation of motion coupled cluster (EOM-SF-CC) can correctly treat situations involving electronic degeneracies or near degeneracies, e. g., bond breaking, di- and tri-radicals, etc. However, for large systems EOM-SF-CC (even in single and double excitations) is computationally prohibitively expensive. Therefore, earlier approximations to EOM-SF-CC methods such as spin flip configuration interaction singles with perturbative doubles (SF-CIS(D)) have been proposed. In this work, we present a new perturbative approximation to EOM-SF-CC, which has been found to be more accurate than SF-CIS(D). The capabilities, advantages, and timings of the new approach have been demonstrated considering the singlet-triplet gaps in di- and triradicals as well as bond breaking examples. The method is extended to double spin flip EOM-CC and its capabilities have been tested. (C) 2013 AIP Publishing LLC.

Excited state geometry optimisation using fock-space multi-reference coupled cluster method - Dutta, Achintya Kumar; Bhattacharya, Sumantra (Molecular Physics, 2014)
The Fock-space multi-reference coupled cluster method is used for the geometry optimisation of the low-lying excited states of the molecules. Molecular geometries of the carbon monohydride cation (CH)(+), water (H2O), ozone (O-3) and formaldehyde (HCHO) in their low-lying excited states are optimised. Excited state gradients are calculated using finite field multi-reference coupled cluster method. We compare our results with other theoretical and/or experimental results, wherever available.
Keywords: adiabatic excitation energy; excited state; Fock-space multi-reference coupled cluster; geometry optimisation; numerical derivative

Ground state of naphthyl cation: singlet or triplet? - Dutta, Achintya Kumar; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2014)
We present a benchmark theoretical investigation on the electronic structure and singlet- triplet(ST) gap of 1- and 2-naphthyl cations using the CCSD(T) method. Our calculations reveal that the ground states of both the naphthyl cations are singlet, contrary to the results obtained by DFT/B3LYP calculations reported in previous theoretical studies. However, the triplet states obtained in the two structural isomers of naphthyl cation are completely different. The triplet state in 1-naphthyl cation is (pi,sigma) type, whereas in 2-naphthyl cation it is (pi,sigma) type, The S-T gaps in naphthyl cations and the relative stability ordering of the singlet and the triplet states are highly sensitive to the basis set quality as well as level of correlation, and demand for inclusion of perturbative triples in the coupled-cluster ansatz. (c) 2014 AIP Publishing LLC.

Intermediate hamiltonian fock space multireference coupled cluster approach to core excitation spectra - Dutta, Achintya Kumar; Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
The Fock space multireference coupled cluster (FSMRCC) method provides an efficient approach for the direct calculation of excitation energies. In intermediate Hamiltonian (IH-FSMRCC) formulation, the method is free from intruder state problems and associated convergence difficulties, even with a large model space. In this paper, we demonstrate that the IH-FSMRCC method with suitably chosen model space can be used for the accurate description of core excitation spectra of molecules, and our results are in excellent agreement with the experimental values. We have investigated the effect of choice of model space on the computed results. Unlike the equation-of-motion (EOM)-based method, the IH-FSMRCC does not require any special technique for convergence and in singles and doubles approximation gives a performance comparable to that of the standard EOMEE-CCSD method, even better in some of the cases.

Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.

Structure, stability, and properties of the trans peroxo nitrate radical: the importance of nondynamic correlation - Dutta, Achintya Kumar; Dar, Manzoor; Vaval, Nayana; Pal, Sourav (Journal of Physical Chemistry A, 2014)
We report a comparative single-reference and multireference coupled-cluster investigation on the structure, potential energy surface, and IR spectroscopic properties of the trans peroxo nitrate radical, one of the key intermediates in stratospheric NOx chemistry. The previous single-reference ab initio studies predicted an unbound structure for the trans peroxo nitrate radical. However, our Fock space multireference coupled-cluster calculation confirms a bound structure for the trans peroxo nitrate radical, in accordance with the experimental results reported earlier. Further, the analysis of the potential energy surface in FSMRCC method indicates a well-behaved minima, contrary to the shallow minima predicted by the single-reference coupled-cluster method. The harmonic force field analysis, of various possible isomers of peroxo nitrate also reveals that only the trans structure leads to the experimentally observed IR peak at 1840 cm(-1). The present study highlights the critical importance of nondynamic correlation in predicting the structure and properties of high-energy stratospheric NOx radicals.

Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

EOMIP-CCSD(2)*: an efficient method for the calculation of ionization potentials - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2015)
A new approximation within the domain of EOMIP-CC method is proposed. The proposed scheme is based on the perturbative truncation of the similarity transformed effective Hamiltonian matrix. We call it the EOMIP-CCSD(2)* method, which scales as noniterative N-6 and its storage requirement is very less, compared to the conventional EOMIP-CCSD method. The existing EOMIP-CCSD(2) method has a tendency to overestimate the ionization potential (IP) values. On the other hand, our new strategy corrects for the problem of such an overestimation, which is evident from the excellent agreement achieved with the experimental values. Furthermore, not only the ionization potential but also geometry and IR frequencies of problematic double radicals are estimated correctly, and the results are comparable to the CCSD(T) method, obviously at lesser computational cost. The EOMIP-CCSD(2)* method works even for the core ionization and satellite IP, where the earlier EOMIP-CCSD(2) approximation dramatically fails.

New scheme for perturbative triples correction to (0,1) sector of Fock space multi-reference coupled cluster method: Theory, implementation, and examples - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
We propose a new elegant strategy to implement third order triples correction in the light of many-body perturbation theory to the Fock space multi-reference coupled cluster method for the ionization problem. The computational scaling as well as the storage requirement is of key concerns in any many-body calculations. Our proposed approach scales as N-6 does not require the storage of triples amplitudes and gives superior agreement over all the previous attempts made. This approach is capable of calculating multiple roots in a single calculation in contrast to the inclusion of perturbative triples in the equation of motion variant of the coupled cluster theory, where each root needs to be computed in a state-specific way and requires both the left and right state vectors together. The performance of the newly implemented scheme is tested by applying to methylene, boron nitride (B2N) anion, nitrogen, water, carbon monoxide, acetylene, formaldehyde, and thymine monomer, a DNA base. (C) 2015 AIP Publishing LLC.

Perturbative order analysis of the similarity transformed hamiltonian in fock-space coupled cluster theory: difference energy and electric response properties - Bhattacharya, Debarati; Dutta, Achintya Kumar; Gupta, Jitendra; Pal, Sourav (Molecular Physics, 2015)
A perturbative analysis of the ground-state similarity transformed Hamiltonian and its effect on the various Fock-space coupled cluster (FSCC) sectors is presented through calculation of ionisation potential, electron affinity, excitation energies and response properties. Various truncation schemes of the effective Hamiltonian are presented with explicit form of the defining equations. Based on such a truncation, the approximate methods are labelled as FSCC(n), where n represents the correlation energy of the ionised, electron attached or excited states corrected at least up to nth order within coupled cluster singles and doubles scheme (CCSD). A lower scaling CC2 type of approach (abbreviated as FS-CC2) is compared against the group of FSCC(n) methods for energies. Electric response properties have been compared and contrasted for the two lower scaling methods: FSCC(2) and FS-CC2. The various truncated methods are tested for a number of small molecules. The results obtained from a range of truncated methods are compared against full FSCCSD calculations.
Keywords: electric response properties; Fock space; perturbative order; similarity transformed Hamiltonian

Electron detachment and subsequent structural changes of water clusters - Das, Susanta; Sengupta, Turbasu; Dutta, Achintya Kumar; Pal, Sourav (Journal of Physical Chemistry A, 2016)
A cost-effective equation of motion coupled cluster method, EOMIP-CCSD(2), is used to investigate vertical and adiabatic ionization potential as well as ionization-induced structural changes of water clusters and compared with CCSD(T), CASPT2, and MP2 methods. The moderate N-5 scaling and low storage requirement yields EOMIP-CCSD (2) calculation feasible even for reasonably large molecules and clusters with accuracy comparable to CCSD(T) method at much cheaper computational cost. Our calculations shed light on the authenticity of EOMIP-CCSD(2) results and establish a reliable method to study of ionization energy of molecular clusters. We have further investigated the performance of several classes of DFT functionals for ionization energies of water clusters to benchmark the results and to get a reliable functionals for the same.

Resolution of the identity and cholesky representation of EOM-MP2 approximation: implementation, accuracy and efficiency - Kumar, Dinesh; Dutta, Achintya Kumar; Manohar, Prashant Uday (Journal of Chemical Sciences, 2017)
We present a Resolution of Identity and Cholesky Decomposition Based Implementation of EOM-MP2 approximation. The RI and CD based EOM-MP2 shows significant speed-up and less storage requirement than the conventional canonical version and can be applied to very large systems. The new algorithm used for this implementation eliminates the most storage requiring four-index quantities resulting in the decrease of storage requirement, reduction in I/O penalties and improved parallel performance, at the expense of more floating point operations. Therefore, the speed-up compared to conventional EOM-MP2 method is more prominent in case of EA, EE and SF case where the storage bottleneck is significant than the EOM-IP-MP2 method, where the storage requirement is significantly less. However, the RI/CD based EOM-IP-MP2 can be coupled with frozen natural orbitals to gain further speed-up.
Keywords: CC; CD; Cholesky decomposition; EA; EE; electron attachment; electron correlation; EOM; equation-of-motion; excited state; ionization; IP; MP2; Resolution-of-identity; RI; SF; spinflip

Lower scaling approximation to EOM-CCSD: a critical assessment of the ionization problem - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2018)
In this article, we investigate the performance of different approximate variants of the EOM-CCSD method for calculation of ionization potential (IP), as compared to EOM-CCSDT reference values. None of the lower scaling approximations to the EOM-CCSD method give a consistent performance for valence, inner valence, and core ionization, favoring one, or the other depending on the nature of the approximation used. The parent EOMIP-CCSD method gives superior performance for valence IP but can show large errors for inner valence and core ionization. The problem is particularly severe for core-ionization, where even the EOMIP-CCSDT method cannot provide quantitative accuracy.
Keywords: EOM-CCSD; Ionization potential; lower scaling